An 11-year retrospective study: clinicopathological and survival analysis of gastro-entero-pancreatic neuroendocrine neoplasm. Issue 33 (14th August 2020) - Liu, Hua; Xie, Rongli; Zhao, Zhifeng; Xu, Dan; Yang, Kaige; Ding, Min; Tan, Dan; Liao, Wenqiang; Han, Xujie; Zhang, Jun; Shen, Dongjie; Yuan, Jianmin; et al.
Abstract : Abstract: To investigate the clinicopathological characteristics and relevant prognostic factors of gastro-entero-pancreatic neuroendocrine neoplasm (GEP-NEN), to improve our understanding of GEP-NEN. This was a retrospective analysis of 155 patients (average age 53.7 ± 13.6 years) pathologically diagnosed with GEP-NEN. We analyzed the clinicopathological characteristics, treatment, and prognostic factors of GEP-NEN. The most common primary site was the pancreas (41.9%), followed by the rectum, stomach and duodenum. Most cases were nonfunctional GEP-NENs (149/155) with nonspecific symptoms. TNM stage and histological grade were determined by the latest criteria. Surgical resection was the mainstay of treatment in 150 patients, and 22 patients received chemotherapy under different circumstances. A total of 130 patients were followed up for a median of 44 months, and 1-year and 3-year survival rates were 82.3% and 72.3%, respectively. According to univariate and multivariate analysis, incidental diagnosis, maximum tumor diameter, tumor stage, lymph node and distant metastasis, TNM stage, and histological grade were significantly correlated with overall survival, but histological grade was the only factor confirmed as an independent prognostic factor for long-term survival of GEP-NEN. GEP-NEN, with an increasing trend in incidence, occurred most frequently in the pancreas. Nonfunctional tumors with nonspecific symptoms comprised the majority of cases. The main treatment was surgical resection. Histological grade was confirmed as the only independent prognostic factor.